Geogrid reinforced brick buildings for earthquake disaster mitigations. (June 2022) - Behera, Biplab; Nanda, Radhikesh Prasad
Abstract: In a severe earthquake, the walls of brick buildings experience in-plane shear and out-of-plane bending, leading to diagonal crack and corner failure, respectively. In this study, an experimental investigation was carried out to observe the above damages on brick masonry buildings reinforced with geogrid embedded in bed joint mortar of the walls. It was observed that the geogrid reinforced brick panels showed better shear strength, lateral strength, ductility, etc. A qualitative comparison was made using a sinusoidal shake table test on a one-fourth single-room building model consisting of two sets of corner walls with and without geogrid reinforcement. It was observed that the corner wall without reinforcement showed crack initiation at 0.45 g and complete collapse with over toppling of the transverse wall at 0.90 g. In contrast, no sign of damages for the corner walls strengthened with geogrid reinforcement for any level of shaking.